Magnitude and impact of genetic heterogeneity on nutritional and fodder quality traits in segregating population of fodder maize (Zea mays L.) - Pawan, K D; Ganesan, K N; Manivannan, N; Vellai, K S; Senthil, N; Pravukalyan, M (Plant Science Today, 2025)
Green fodder, a vital and cost-effective source of animal nutrition, plays a crucial role in sustaining livestock productivity. However, the limited availability of nutritionally rich green fodder poses a major constraint in India, underscoring the need for genetic improvement in forage crops, such as maize. To address this, the present investigation focused on evaluating genetic variability in F3 progenies segregating for biomass yield and nutritional quality traits in fodder maize. The study revealed that several progenies exhibited significantly higher mean values for key traits compared to the better parent, African Tall. High heritability and genetic advance were recorded for plant height (PH), leaf length (LL), leaf breadth (LB), internode length (INL), crude protein (CP), acid detergent fiber (ADF), dry matter yield (DMY) and green fodder yield (GFY), indicating the predominance of additive gene action and the effectiveness of selection based on these traits. Correlation analysis revealed that all biomass yield components were positively correlated with GFY, except for leaf stem ratio (LSR), which showed a significant negative correlation. Nutritional traits, such as CP and ADF showed no significant association with GFY, while crude fiber (CF) and neutral detergent fiber (NDF) exhibited significant negative correlation. Notably, CF, ADF and NDF were positively correlated with each other but negatively associated with CP. DMY, PH and stem girth (SG), demonstrated significant positive correlation, as well as a high positive direct effect on GFY, indicating a true relationship that could be taken as a component trait for GFY improvement. Therefore, a selection index comprising traits such as PH, LL, LB, SG, INL, CP and DMY would be effective in improving both biomass yield and nutritional quality in fodder maize.